ANALISIS FAKTOR YANG MEMPENGARUHI TINGKAT PENGUNGKAPAN SUKARELA ASET TAK BERWUJUD (Studi pada Perusahaan yang Terdaftar di BEI Tahun 2010-2012) - Anggrahini Dyah Perwitasari; Aditya Septiani (Diponegoro Journal of Accounting, 2014)
This study aims to analyze the influence of firm size, ownership concentration, leverage, industry type, price-to-book value, age of firm, and auditor type on the level of intangible assets disclosure in annual reports in Indonesia. To measure the level of intangible assets disclosure used Value Chain Scoreboard™ as a framework disclosure for intangible assets that was developed by Kang and Gray. There are 28 items to detect quality of intangible assets disclosure. Object in this study are the companies that listed in Indonesia Stock Exchange (ISX) and include in 50 biggest market capitalization during 2010-2012. The sample was selected using purposive sampling method and obtained thirty seven companies being sampled. Type of data are secondary data, as annual reports of companies. Data analysis used descriptive statistics, classical asumption test, and multiple liniar regression analysis. The result of this study showed that ownership concentration, leverage, industry type, price-to-book value, and age of firm significantly influence to the level of intangible assets voluntary disclosure. Meanwhile, firm size and auditor type had no significant effect to the level of intangible assets voluntary disclosure.